Optimization of phosphorus level for effective arbuscularmycorrhizal activity in rainfed upland rice based cropping system - MANOJ KUMAR BARNWAL, DIPANKAR MAITI* and (Indian Phytopathology, 2012)
Direct seeded upland rice (Oryza sativa L.), grown under aerobic soil conditions of rainfed, drought prone ecology is Â constrained by poor phosphorus (P) acquisition. Arbuscular-mycorrhiza (AM) supportive rice based crop rotations under this AM favorable ecology was demonstrated to improve AM aided P nutrition in upland rice. The present investigation aimed at optimizing P dose for possible further enhancing native AM-fungi (AMF) aided P acquisition of upland rice under AM supportive crop rotations. Under highly AM supportive, two year crop rotation of â€˜maize (Zea mays L.) relay cropped by horse gram (Dolichos biflorus L.) in first year followed by rice in second yearâ€™, 20 kg P2O5/ha (to rice) enhanced AMF population (+79%) in soil during rice sowing (June), leading to significantly higher average (two years) AMF colonization (+15.3 %), P uptake (+10.1%) with concomitant increase in grain yield (+30.4%) over that of recommended dose (30 kg P2O5/ha).